2003
DOI: 10.1017/s1355617703970081
|View full text |Cite
|
Sign up to set email alerts
|

The basal ganglia and semantic engagement: Potential insights from semantic priming in individuals with subcortical vascular lesions, Parkinson's disease, and cortical lesions

Abstract: The impact of basal ganglia dysfunction on semantic processing was investigated by comparing the performance of individuals with nonthalamic subcortical (NS) vascular lesions, Parkinson's disease (PD), cortical lesions, and matched controls on a semantic priming task. Unequibiased lexical ambiguity primes were used in auditory prime-target pairs comprising 4 critical conditions; dominant related (e.g., bank-money), subordinate related (e.g., bank-river), dominant unrelated (e.g., foot-money) and subordinate un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 59 publications
(91 reference statements)
8
90
0
3
Order By: Relevance
“…In a word pair priming task containing ambiguous words as primes, the NS and PD groups continued to prime both the dominant and subordinate meanings of an ambiguous word at a long interval between prime and target. Copland (2003) interpreted the findings as reflecting a deficit in selective attentional engagement possibly implicating deficits in frontal-subcortical systems related to inhibitory semantic mechanisms.…”
Section: Language Processing In Individuals With Damage To the Basal mentioning
confidence: 99%
See 2 more Smart Citations
“…In a word pair priming task containing ambiguous words as primes, the NS and PD groups continued to prime both the dominant and subordinate meanings of an ambiguous word at a long interval between prime and target. Copland (2003) interpreted the findings as reflecting a deficit in selective attentional engagement possibly implicating deficits in frontal-subcortical systems related to inhibitory semantic mechanisms.…”
Section: Language Processing In Individuals With Damage To the Basal mentioning
confidence: 99%
“…Inhibitory deficits in patients with LFC damage are a recurring theme in the literature and are referred to again in studies of patients with PD and patients with nonthalamic subcortical (NS) vascular lesions (Copland, 2003). In a word pair priming task containing ambiguous words as primes, the NS and PD groups continued to prime both the dominant and subordinate meanings of an ambiguous word at a long interval between prime and target.…”
Section: Language Processing In Individuals With Damage To the Basal mentioning
confidence: 99%
See 1 more Smart Citation
“…Moro et al, 2001;Friederici et al, 2003), semantic (e.g. Pilgrim et al, 2002;Copland, 2003) and prosodic components (e.g. Brådvik et al, 1991;Breitenstein et al, 1998Breitenstein et al, , 2001Pell and Leonard, 2003;P eron et al, 2013).…”
Section: Basal Gangliamentioning
confidence: 99%
“…Indeed, studies investigating striatal damaged patients have shown various kinds of language disorders ranging from semantic disorganisation to syntactic impairment in both neurodegenerative diseases such as Huntington's and Parkinson's disease (e.g., Copland, 2003;Frank, McDade, & Scott, 1996;Illes, 1989) and in patients with vascular damage (e.g., Damasio, Damasio, Rizzo, Varney, & Gersh, 1982;Wallesch & Papagno, 1988). This might be related to the different lesion patterns regarding the different aetiologies: vascular disorders affect various parts of the striatum and often involve surrounding white matter fibre tracks, Parkinson's disease (PD) is due to neural degeneration in the substantia nigra resulting in dopamine-related dysfunction of the striatum, whereas Huntington's disease (HD) is characterised by neuronal death that specifically originates in the neostriatum comprising the caudate head and the putamen (see Peschanski, Cesaro, & Hantraye, 1995 for a review).…”
Section: Introductionmentioning
confidence: 99%